KAJIAN PAJAK TERHADAP DUA BENTUK BADAN USAHA - Anisah Anisah (Universitas Batanghari Jambi, 2016)
This research intends to reveal the differences between two different kinds of corporation (PT and CV) from the tax imposition aspects. Those are the Income Tax, Land and Building, and Value added tax. The financial report data of the company used to support this research and it comes from one financial report data so that we can see a clear differences in the amount of financial report between PT and CV.From this research, it can be concluded that there will be different imposition of taxation if the type of the corporation is different too. The difference is only at the moment when the company expending money to the owner, that used for salary or dividend. Although the taxation differences only come from the income tax, but those differences can be used as consideration when we want to determine the type of the corporation.Key words : the differences between PT and CV from taxation aspects